Combined effect of magnetic field and hydrostatic pressure on the phase transitions exhibited by Ni-Mn-In metamagnetic shape memory alloy. (July 2020) - Lázpita, P.; L'vov, V.A.; Fernández, J. Rodríguez; Barandiarán, J.M.; Chernenko, V.A.
Abstract: We present a systematic study of the magnetostructural and magnetic transitions in the prototype metamagnetic shape memory alloy Ni50 Mn34.5 In15.5 under hydrostatic pressure and combined pressure and magnetic field. Pressure extends the area of stability of the antiferromagnetic martensitic phase. At low magnetic field the pressure derivatives of the Curie temperatures of austenite, T CA, and martensite, T CM, show opposite signs. This fact is described in the framework of the Landau thermodynamic model as arising from a weak long-range antiferromagnetic state of martensite. Two volume magnetoelastic constants were estimated using the experimental values of the pressure derivatives of T CA and T CM . A correlation between the signs of the pressure shifts of T CA, and T CM and the distance between Mn-Mn nearest neighbours is established, which matches the empirical Castelliz-Kanomata diagram. The entropy change at martensitic transformation (MT), Δ SMT, grows up when the MT temperature, TM, is approaching TCA under the influence of pressure, but under constant non-zero pressure this dependence is inverse. Graphical abstract: Image, graphical abstract